Palavra de Deus no Antigo e Novo Testamento - Stadelmann, Luís (Revista Eclesiástica Brasileira, 2011)
O artigo começa com a investigação do problema da hermenêutica da palavra de Deus, na época do movimento do “modernismo”, no fim do séc. XIX e no começo do séc. XX. Uma visão de conjunto da Sagrada Escritura trata dos livros da Bíblia como literatura funcional. A seguir, são abordados os arautos da palavra de Deus no AT e NT e seu papel na comunidade de fé. A influência da palavra de Deus, na faculdade do intelecto e da vontade, é determinante no comportamento humano. A tipicidade cultural do mundo hebraico e helênico desvenda os traços significativos dos respectivos livros bíblicos. Por fim, se analisa o prólogo do Evangelho de João para apresentar a pessoa de Jesus Cristo, como personificação da Palavra de Deus na vida trinitária e na relação com a humanidade. Abstract: The article begins by investigating the problem of hermeneutics concerning the word of God in connection with the crisis of the movement of “modernism” at the end of the 19th and the beginning of the 20th century. A comprehensive view of the Sacred Scriptures envisages the books of the Bible as functional literature. The following chapter focuses upon the messengers of the word of God in the OT and NT with special attention taking into account their role in the faith community. Further, the influence of the word of God on one’s intellect and will is studied so as to find out why they make their each and every move determining human behavior. New insight is to be gained by working out the literary approach of the word of God in the context of disparate cultures and diverse differentiations which occurred both in Hebraic and Hellenistic thought patterns, which are exemplified in the biblical books of the OT and NT. In the final chapter the personified word of God by Jesus Christ is considered by a detailed analysis of the Prologue of the Gospel of John in order to ascertain the divine role within the Trinity and in the relationship between God and the world.